Penggunaan Ultra High Frequency RFID pada Sistem Inventarisasi Creatrix Organizer - Welly Tedja Kusuma; Yulia Yulia; Resmana Lim (Jurnal Infra, 2020)
At this moment, Event Organizer Creatrix Organizer records its items manually. Creatrix Organizer have not used structural system to record the items yet. Creatrix Organizer always having trouble to find the item for small scale event. The small-scale events does not require all the items from the warehouse and take time to find the items needed for the event. This situation will result in a delayed process. The customer will not be satisfied because the work is not optimal. Based on the Creatrix Organizer problem, the authors design a system that can record and count items automatically using Ultra High Frequency (UHF) Radio Frequency Identification (RFID). Not only tool, but also a website using CodeIgniter Framework and smartphone application using Ionic Framework for worker to make their job easier to find the needed items for the event. The database used for the applications is MySQL.The results of the applications are, they can record and count the items automatically using UHF Radio Frequency Identification (RFID). Furthermore, they can record and search the items that available in the website. Smartphone application is used for searching the items that available to use.